Magnetorheological energy absorber with dual concentric annular valves. (April 2016) - Bai, Xian-Xu; Wereley, Norman M; Choi, Young-Tai
For semi-active shock and vibration mitigation systems using magnetorheological energy absorbers, fail-safe performance is of particular significance if electric power is lost. At the same time, the minimization of the field-off damping force of the magnetorheological energy absorbers at high speed is also important because the damping force due to the viscous damping force at high speed becomes too excessive, and thus, the controllable dynamic range is rapidly reduced. In this article, a fail-safe magnetorheological energy absorber with dual concentric annular valves and an inner-set permanent magnet is proposed to decrease the field-off damping force while keeping an appropriate dynamic range for improving shock and vibration mitigation performance. In the magnetorheological energy absorber, the dual concentric annular valves are configured so as to decrease the baseline damping force, and magnetic activation methods using the electromagnetic coil winding and the permanent magnet are used to maintain appropriate magnetic intensity in these concentric annular valves. An initial field-on damping force is produced by the magnetic field bias generated from the inner-set permanent magnet in consideration of the failure of the electric power supply. The initial field-on damping force of the magnetorheological energy absorbers can be increased (or decreased) by applying positive (or negative) current to the electromagnetic coil winding, and thus, bidirectional controllable damping performance could be realized. After establishing the analytical damping force model of the magnetorheological energy absorber using a Bingham-plastic nonlinear fluid model, its working principle and magnetic properties are analytically validated and analyzed via electromagnetic finite element analysis. The performance of the magnetorheological energy absorber is also theoretically compared with that of a conventional magnetorheological energy absorber with a single valve with the constraint of an identical volume under different excitation velocities.